Factors cause the failure of policy implementation of traditional customary governance system (Nagari) in West Sumatera Province, Indonesia - Yulivestra, Malse; Zauhar, Soesilo; Wijaya, Andy Fefta; Hidayati, Firda (Edelweiss Applied Science and Technology, 2025)
This study examines the persistent non-implementation of West Sumatra Provincial Regulation Number 7 of 2018 concerning the return to a traditional nagari governance system in Indonesia. Despite its enactment, no district-level government within the province has translated the regulation into enforceable local policy. This phenomenon presents a significant gap between policy formulation and implementation. Employing a qualitative-descriptive methodology, data were collected through interviews, observations, and document analysis, then triangulated and interpreted using both etic and emic perspectives. The research adopts several theoretical lenses, including the policy implementation models of Van Meter and Van Horn, Edwards III, Grindle, and Mazmanian & Sabatier, to understand the multidimensional challenges. Findings reveal four primary factors hindering implementation: (1) overly optimistic expectations that overlook diverse local customs ("adat salingka nagari"), (2) dispersed governance systems that complicate vertical coordination, (3) insufficient stakeholder involvement during policy formulation, and (4) political cycle uncertainties and limited political will at sub-national levels. These barriers underscore a disconnect between elite-driven top-down policymaking and the participatory, context-sensitive governance structures embedded in Minangkabau society. The study concludes that successful implementation of such context-specific governance reforms requires tailored derivative regulations at district and city levels, inclusive policy design involving local actors, and robust intergovernmental coordination. This research contributes to broader discourses on policy implementation gaps in decentralized governance systems and the challenges of harmonizing legal frameworks with indigenous political traditions.